Vehicle Communication Experiment Environment with MANET and NEMO - Tsukada, M.; Ernst, T. (2007 International Symposium on Applications and the Internet Workshops, 2007)
Mobile adhoc network (MANET) routing protocols and NEMO basic support protocol are developed as independent technologies. Since both will be used in vehicles communication, interaction between MANET and NEMO (MANEMO) brings benefits which are referred as route optimization and multihoming. To investigate MANEMO, we classify it into five topologies. With Optimized Link State Routing (OLSR) protocol and NEMO basic support protocol, we setup a real-field testbed which consist of mobile networks in two electric vehicles. Network performance of MANEMO is evaluated with this testbed. The experimentation results show that MANEMO allows to improve the overall network performance